Learning to Fiddle in a Community of Practice - Landry, Rachelle; Stark, Jody (MUSICultures, 2023)
This article explores some of the specific dynamics and processes experienced by Canadian old-time fiddlers as they learn to fiddle in a community of practice (CoP). Based on an analysis of interviews with several fiddlers at the Kenosee Lake Kitchen Party fiddling camp, we explore two elements of fiddling that the fiddlers identified as crucial to the development of expertise as an old-time fiddler: a danceable quality and personalizing a tune. Danceability allowed for historical continuity of the community’s practices, while making a tune your own provided a way to introduce new ideas and practices into the CoP, resulting in growth and change.